Non-p53 p53RE binding protein, a human transcription factor functionally analogous to P53 - Zeng, Xiaoya (The National Academy of Sciences, 1998)
The transactivation activity of the p53 tumor suppressor protein is critical for regulating cell growth and apoptosis. We describe the identification of a transcription factor that is functionally similar to p53 and contains the same DNA binding and transcription activities specific for the p53 responsive DNA element (p53RE). This protein was highly purified through chromatography from HeLa cell extracts. The purified protein was able to bind specifically to the p53RE derived from a p21(waf1) promoter and to stimulate p53RE-dependent transcription but not basal transcription in vitro. Its DNA-binding activity was inhibited by the wild type but not mutant p53RE-containing DNA oligomers. Also, this p53RE-binding activity was found in human p53 null Saos-2 osteosarcoma and H1299 small cell lung carcinoma cells. Interestingly, this activity exhibited a p53RE sequence preference that was distinct from the p53 protein. The activity is neither p53 nor p73, because anti-p53 or anti-73 antibodies were unable to detect this purified protein nor were the antibodies able to alter the p53-like activity, the p53RE-protein complex. These results demonstrate that, besides p73, an additional p53-like protein exists in cells, which is named NBP for non-p53, p53RE binding protein.